Formulation and In Vitro Evaluation of Meloxicam-Loaded Transdermal Patches: Effect of Polymeric Blends on Drug Release and Kinetics - Ameen M. Alwossabi; Imad M. Taj Eldin; Ahmed M. Al-Ghani; Mohammed Abdelrahman; Ahmed Ashour; Wadah Osman; Mohammed Hamed Alqarni; Ahmed I. Foudah; Mohamed Abdel-Monem El- Sakhawy; Reham M. Samra (Natural Resources for Human Health, 2026)
Meloxicam taken orally is linked to adverse reactions in the gut and varying bioavailability because of first-pass metabolism. Because they allow for prolonged drug release and increased therapeutic efficacy, transdermal drug delivery systems (TDDS) offer a promising alternative. Using various polymeric blends, the current work sought to create and assess meloxicam-loaded transdermal patches in order to maximize their physicochemical characteristics and drug release behavior. Polyvinyl alcohol or polyvinylpyrrolidone in conjunction with hydroxypropyl methylcellulose was used in the solvent evaporation process to create meloxicam patches for the skin. Thickness, weight deviation, folding endurance, expansion index, contact pH, homogeneity of drug content, and in vitro drug diffusion in the presence of phosphate buffer (pH 7.4) were all assessed for six formulations (F1–F6). Drug–polymer compatibility was assessed using Fourier transform infrared spectroscopy (FTIR). Release kinetics were analyzed using mathematical models. All formulations exhibited acceptable physicochemical characteristics and surface pH compatible with skin application. Among the tested formulations, F1 (HPMC: PVA, 3:1) demonstrated the highest cumulative drug release (92% over 12 h) along with good drug content uniformity and stable mechanical properties. FTIR analysis confirmed the absence of chemical interactions between meloxicam and the polymers. Kinetic modeling indicated that drug release predominantly followed diffusion-controlled and non-Fickian mechanisms. Conclusion: The optimized formulation (F1) showed favorable performance as a matrix-type transdermal patch for sustained meloxicam delivery. These findings highlight the influence of polymeric composition on drug release behavior and support the potential of transdermal systems as an alternative to oral meloxicam therapy.